Internet Workshops - Beverley E. Crane (Neal-Schuman Publisher, 2003)
This book explain about what does research tell us about learning? what do we know about profesional development?using search tools, using communication tools, evaluating web sites, creating internet-based lessons for the english-language arts curiculum, creating internet-based lessons for the social studies curriculum, creating web pages, employing advanced internet technique.